Detección de factores de riesgo modificables no conocidos previamente en pacientes con evc isquémico ingresados en los hospitales del minsa de la ciudad de trujillo durante el periodo marzo - noviembre del año 2014 - Terrones Villalobos, Dany Joel (2016)
There are a number of modificable stroke risk factors such as hypertension, diabetes mellitus, dyslipidemia, and atrial fibrillation, whose recognition and control an essential to reduce the occurrence of cerebrovascular disease. Sometimes the stroke may be the presenting symptom of these risk factors. Object: A prospective observational study of patients admitted at HRDT and HBT for ischemic cerebrovascular disease, to know the percentage of patients with hypertension, diabetes mellitus, dyslipidemia and previously undiagnosed atrial fibrillation. Results: 73 patients, of whom 13 had unknown arterial hypertension (17.8%) was selected; 7 unknown diabetes mellitus (9.6%); 29, unidentified hypercholesterolemia (39.7%); 8 hypertriglyceridemia not known (10.9%), and 10 had no known atrial fibrillation (13.7%). In total, 43 patients (58.9%) had any of these risk factors for stroke. The existence of a risk factor not previously diagnosed was greater in rural areas. Hypertension and atrial fibrillation associated mostly development of lacunar infarcts (44.4%) and partial anterior circulation infarction (56.7%), respectively; both with statistical significance (p <0.005). Conclusion: More than half of the subjects who suffer a cerebrovascular event have a risk factor that has not been previously diagnosed, being more frequent in rural areas